Influence of cardoon flower (cynara cardunculus L.) and flock lactation stage in PDO Serra da Estrela cheese - Fogeiro, Élia (2020)
Serra da Estrela (SE) cheese is one of the most appreciated Portuguese cheeses, being produced only from raw ewe's milk, cardoon flower and salt. Cardoon takes part in two important processes in cheese production-coagulation and proteolysis-contributing to its unique features. Furthermore, milk chemical characteristics change during the milking season, being another factor that account for the high variability of cheese attributes. Therefore, the purpose of this work is to study the influence of cardoon flower (commercial, 6 M and 3 M) and flock lactation stage (November 2018, February and April 2019) in the final characteristics of SE cheese. The parameters analysed were moisture, protein, fat and salt contents, texture and colour. Results showed that flock lactation stage has the highest influence in all the studied characteristics, corresponding the early stages of lactation to the most protein-rich and low-fat cheeses. Cardoon flower affects mainly fat and rind colour. This study allows us to conclude that seasonal changes in ewe's milk have a considerable impact in cheese attributes, and that although cardoon type had a more restrained effect, when used with expertise it may help adjust cheese sensory characteristics in order to obtain a final product that matches consumer acceptability requirements.